2003
DOI: 10.1074/jbc.m306325200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Functionally Critical Protein Kinase C Phosphorylation Residue of Cardiac Troponin T

Abstract: Cardiac Troponin T (cTnT) is one prominent substrate through which protein kinase C (PKC) exerts its effect on cardiomyocyte function. To determine the specific functional effects of the cTnT PKC-dependent phosphorylation sites (Thr197, Ser201, Thr206, and Thr287) we first mutated these residues to glutamate (E) or alanine (A). cTnT was selectively mutated to generate single, double, triple, and quadruple mutants. Bacterially expressed mutants were evaluated in detergent-treated mouse left ventricular papillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
244
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(258 citation statements)
references
References 58 publications
13
244
1
Order By: Relevance
“…Myosin-S1 was made by chymotryptic digestion of rabbit psoas muscle myosin. Recombinant mouse cTnI (wild-type and mutant) in pET3d, mouse cTnT containing an N-terminal myc tag in pSBET, and human cTnC in pET3d were expressed and purified as described previously (20,25). It was shown that myc tag at the N terminus of cTnT has no effect on myofilament activity (20).…”
Section: Methodsmentioning
confidence: 99%
“…Myosin-S1 was made by chymotryptic digestion of rabbit psoas muscle myosin. Recombinant mouse cTnI (wild-type and mutant) in pET3d, mouse cTnT containing an N-terminal myc tag in pSBET, and human cTnC in pET3d were expressed and purified as described previously (20,25). It was shown that myc tag at the N terminus of cTnT has no effect on myofilament activity (20).…”
Section: Methodsmentioning
confidence: 99%
“…A more direct study in which transgenic mice lacking PKC phosphorylation sites expressed approximately 50% fast skeletal TnT (fsTnT) provided evidence for a potential role of cTnT phosphorylation in depressing/reducing myofilament force (Montgomery et al 2001). Sumandea et al (2003) studied the specific functional effects by charge mutating the cTnT sites (Thr197, Ser201, Thr206, Thr287, mouse sequence) into aspartic acid and replacing the recombinant cTn into detergent-treated mouse LV papillary muscle fibers. Phospho-mimicking of Thr206, but not the other sites, in the TG mice resulted in decreased maximal tension, actomyosin Mg-ATPase activity, Ca 2+ -sensitivity, and cooperativity (Table 1).…”
Section: Ser275mentioning
confidence: 99%
“…However, it does contain up to four potential PKC-specific phosphorylation sites [73]. Sumandea et al, employing recombinant Tn exchange techniques in skinned myocardium, demonstrated that Thr-206 is the functionally important site [73].…”
Section: Troponin Tmentioning
confidence: 99%
“…However, it does contain up to four potential PKC-specific phosphorylation sites [73]. Sumandea et al, employing recombinant Tn exchange techniques in skinned myocardium, demonstrated that Thr-206 is the functionally important site [73]. That is, either phosphorylation or a charge mutation phospho-mimic (Thr206Glu) at this residue significantly reduces maximum Ca 2+ -saturated force, myofilament Ca 2+ sensitivity, and crossbridge cycling rate.…”
Section: Troponin Tmentioning
confidence: 99%
See 1 more Smart Citation